Detection and partial characterization of antifungal bioactivity from the secretions of the medicinal maggot, Lucilia sericata. Issue 3 (9th June 2015) - Evans, Rhys; Dudley, Ed; Nigam, Yamni
ABSTRACT The antibacterial properties of the excretions/secretions (ES) of the medicinal maggot, Lucilia sericata have long been known and the effectiveness of maggot debridement therapy in relation to the clearance of bacteria from the surface of wounds has been the source of much research over recent years. Less well known, however, are the antifungal properties of L. sericata ES. Here, we show by means of the colony forming unit assay and optical density assays, that L. sericata native ES possess significant antifungal properties and appears to possess a highly heat stable, freeze/thaw, and lyophilization resistant antifungal component. We also show that the antifungal activity present in the native ES consists of a number of antifungal components present in three fraction masses consisting of >10, 10–0.5, and <0.5 kDa, with the greatest level of activity being seen in the <0.5 kDa fraction.